Emerging Trends in IoT and Computing Technologies Proceedings of the International Conference on Emerging Trends in IoT and Computing Technologies (ICEICT-2022), April 22-23, 2022, Lucknow, India - Tripathi, Suman Lata (CRC Press LLC, 2023)
This book includes the proceedings of the International Conference on Emerging Trends in IoT and Computing Technologies (ICEICT-2022) held at Goel Institute of Technology & Management, Lucknow, India
Description based on publisher supplied metadata and other sources
Keywords: Internet of things-Congresses